A solid phase extraction method for isolating HF-extractable soil organic matter for NMR analysis. (September 2017) - Warren, Jamie; Ziegler, Susan E.
Abstract: Cross polarization magic angle spinning 13 C nuclear magnetic resonance (CP-MAS 13 C-NMR) analysis of soil is an important technique for understanding soil organic carbon (SOC) source, cycling and fate. The low carbon concentration in, and paramagnetic interference from, most mineral soils require that they be extracted and demineralized using HF, generating a residue that is analyzed via CP-MAS 13 C-NMR. However, the HF extractable fraction typically represents a significant fraction of the total SOC that cannot be analyzed directly. We describe a method developed for the solid-phase extraction (SPE) of the HF-extractable fraction of SOC from the HF demineralization of mineral soils. Podzolic mineral soils were demineralized with 10% HF, with > 50% of total SOC retained with the existing mineral matrix in the HF-extractable fraction. SPE was utilized to recover and concentrate the HF-extractable SOC as a mineral free extract. Using the approach, 61–73% of the HF extractable SOC was recovered, resulting in a recovery of 73–82% of the total soil SOC. A marked improvement over the 35–51% recovered solely in the HF-insoluble fraction, the soil fraction typically analyzed using CP-MAS 13 C-NMR. The increased carbon content and removal of paramagnetic minerals via SPE greatly improved the CP-MAS 13 C-NMR signal to noise relative to the HF-insoluble SOC fraction. The composition of the SPE recovered, HF-soluble fraction was rich in aromatic and carboxylic C, in addition to specific alkyl and O-alkyl C types, relative to the HF-insoluble fraction. The method should enable insight into an often significant but poorly studied mineral SOC fraction and, through the decreased matrix effect, should improve comparability among different soil and dissolved organic matter (DOM) samples.